Remobilization of zinc in sediments by mangrove and its associated species in Blanakan River, West Java, Indonesia - Noverita Dian Takarina (Society for Indonesian Biodiversity, 2020)
Abstract. Takarina ND. 2020. Remobilization of zinc in sediments by mangrove and its associated species in Blanakan River, West Java, Indonesia. Biodiversitas 21: 1743-1748. The biodiversity of mangrove and associated species have contribution to remove contaminants from aquatic environment, for example, river. This work aims to study the effects of mangrove and associated species in absorbing zinc (Zn) from water and sediment and remobilizing it into stems. The work was conducted by sampling mangroves, associated species, sediment and water along 9 stations in riparian of Blanakan River, West Java. The stems of mangrove and associated species, water and sediments were analyzed for Zn content using AAS. The biodiversity was evaluated using Shannon-Wiener index (H’). The bioremobilization potential was calculated using Bioconcentration Factor (BCF). There were 3 true mangrove species (i.e. Rhizophora mucronata, Avicennia marina, and Sonneratia caseolaris) and 3 mangrove associate species (i.e. Colocasia esculenta, Ipomoea aquatica, and Wedelia biflora). The H’ was ranging from 0.5 to 0.7. We found that the riparian with high species richness and biodiversity has less Zn contents both in water and sediments, while the riparian that has low species diversity has high Zn in water and sediments. All the mangrove and associated species have stored Zn in their stems with the most effective species in remobilizing Zn from water and sediment were C. esculenta, S. caseolaris, and R. mucronata. The contamination of Zn in aquatic ecosystem can be managed and reduced by increasing mangrove and associated species diversity and planting species that effective in remobilization of contaminants from environment.